Arts and cultural management : sense and sensibilities in the state of the field - DeVereaux, Constance (Routledge, an imprint of the Taylor & Francis Group, 2019)
"Arts and Cultural Management: Sense and Sensibilities in the State of the Field opens a conversation that is much needed for anyone identifying arts management or cultural management as primary areas of research, teaching, or practice. In the evolution of any field arises the need for scrutiny, reflection, and critique, as well as to display the advancements and diversity in approaches and thinking that contribute to a discipline's forward progression. While no one volume could encompass all that a discipline is or should be, a representational snapshot serves as a valuable benchmark. This book is addressed to those who operate as researchers, scholars, and practitioners of arts and cultural management. Driven by concerns about quality of life, globalization, development of economies, education of youth, the increasing mobility of cultural groups, and many other significant issues of the twenty-first century, governments and individuals have increasingly turned to arts and culture as means of mitigating or resolving tough policy issues. For their growth, arts and culture sectors depend on people in positions of leadership and management who play a significant role in the creation, production, exhibition, dissemination, interpretation, and evaluation of arts and culture experiences for publics and policies. Less than a century old as a formal field of inquiry, however, arts and cultural management has been in flux since its inception. What is arts and cultural management? remains an open question. A comprehensive literature on the discipline, as an object of study, is still developing. This State of the Discipline offers a benchmark for those interested in the evolution and development of arts and cultural management as a branch of knowledge alongside more established disciplines of research and scholarship."-Resumé vydavatel
Keywords: management umění; umění a společnost; management kultury; arts management; art and society; cultural management; elektronické knihy; sborníky; electronic books; papers of several authors